Outcome of recycle bone reconstruction using liquid nitrogen in primary malignant bone tumor - Ramadian, Nurul; Mahyudin, Ferdiansyah; Edward, Mouli; Basuki, Mohammad Hardian; Bari, Yunus Abdul (Edelweiss Applied Science and Technology, 2024)
Primary malignant bone tumors constitute a small but significant portion, accounting for 3–5% of childhood cancers. Cryosurgery, utilizing liquid nitrogen to induce tumor necrosis through extreme cold, emerges as a favorable surgical technique for bone tumor. This study delves into the clinical and radiological outcomes of individuals underwent cryosurgery. This descriptive study focused on patients with primary malignant bone tumors subjected to wide resection and cryosurgery with follow-up period from 6 up to 48 months from year 2018 - 2023. The data was collected from medical records and database, we evaluated the demographic data, clinical with Musculoskeletal Tumor Society (MSTS), radiological outcome with International Society of Limb Salvage (ISOLS) score, and the complications of cryosurgery observed. Among the 37 patients examined, 20 males and 17 females were averaging 21.7 years of age. 29 of 37 (78%) cases identified as osteosarcoma most common location in the epimetaphyseal of the long bone with Grade Enneking IIB. MSTS score averaged 25.35 ± 5.54, with more than 68% achieving excellent and good score. ISOLS for radiological score revealed 37.8% with an excellent score, 48.6% with a good score. The most common complication, reccurence, occurs in 6 cases (16.2%). Patients with primary malignant bone tumors who underwent cryosurgery showed successful clinical and radiological outcomes, as measured by MSTS and ISOLS scores. This underscores the significance of cryosurgery in primary malignant bone tumor as favorable and cost-effective treatment, showcasing improved functionality and positive radiological results.